Design for additive manufacturing with site-specific properties in metals and alloys. (1st July 2017) - Tammas-Williams, S.; Todd, I.
Abstract: Intelligent application of materials with site-specific properties will undoubtedly allow more efficient components and use of resources. Despite such materials being ubiquitous in nature, human engineering structures typically rely upon monolithic alloys with discrete properties. Additive manufacturing, where material is introduced and bonded to components sequentially, is by its very nature a good match for the manufacture of components with changes in property built-in. Here, some of the recent progress in additive manufacturing of material with spatially varied properties is reviewed alongside some of the challenges facing and opportunities arising from the technology. Graphical abstract: